Death and burial in medieval England: 1066-1550 - Daniell, Christopher (Routledge, Taylor & Francis Group, 2026)
"This volume offers readers a comprehensive and vivid picture of medieval death and burial in England, bringing the fascinating beliefs and rituals surrounding mortality into sharp focus. Death had a pervasive presence in daily medieval English life, finding expression in monuments, literature and art. This book expertly weaves together analysis of historical, archaeological and literary sources to provide a uniquely interdisciplinary look at the entire phenomenon. Now in its second edition, Daniell incorporates the latest findings derived from DNA and isotope analysis, providing readers with a case study of the discovery and results from the skeleton of Richard III. New chapters examine 'deviant' burials and the role of revenants and ghosts, whilst the final chapter introduces new theories regarding the Black Death's transformative societal impact - the heightened desire for small group structures, such as nuclear families or guilds, and the increased centrality of the human body in religious and artistic representation. This book is of value to students, scholars and anyone interested in the history of death, archaeology, anthropology and medieval English life and ritual"-- Provided by publisher